miRNA Signatures in Bronchopulmonary Dysplasia: Implications for Biomarkers, Pathogenesis, and Therapeutic Options - Hajime Maeda; Xiaoyun Li; Hayato Go; Phyllis A. Dennery; Hongwei Yao (Frontiers in Bioscience-Landmark, 2024)
Bronchopulmonary dysplasia (BPD) is a chronic lung disease in premature infants characterized by alveolar dysplasia, vascular simplification and dysmorphic vascular development. Supplemental oxygen and mechanical ventilation commonly used as life-saving measures in premature infants may cause BPD. microRNAs (miRNAs), a class of small, non-coding RNAs, regulate target gene expression mainly through post-transcriptional repression. miRNAs play important roles in modulating oxidative stress, proliferation, apoptosis, senescence, inflammatory responses, and angiogenesis. These cellular processes play pivotal roles in the pathogenesis of BPD. Accumulating evidence demonstrates that miRNAs are dysregulated in the lung of premature infants with BPD, and in animal models of this disease, suggesting contributing roles of dysregulated miRNAs in the development of BPD. Therefore, miRNAs are considered promising biomarker candidates and therapeutic agents for this disease. In this review, we discuss how dysregulated miRNAs and their modulation alter cellular processes involved in BPD. We then focus on therapeutic approaches targeting miRNAs for BPD. This review provides an overview of miRNAs as biomarkers, and highlights potential pathogenic roles, and therapeutic strategies for BPD using miRNAs.